Investigation of Knowledge and Awareness about Food Nanotechnology of Nutrition and Dietetics Students - Muhammet Ali Cakir; Yeliz Mercan (International Journal of Gastronomy Research, 2023)
In this study, it was aimed to examine the knowledge and awareness levels of nutrition and dietetics department students about food nanotechnology. This descriptive study was conducted with 242 students aged 18 and over who were studying at the Department of Nutrition and Dietetics.52.1% of the participants are 22 years old and over, and 66.9% have heard of the concept of food nanotechnology (nano food). In the study, it was determined that the level of knowledge and awareness about food nanotechnology was high among those who had heard of the concept of food nanotechnology (nano food) before (p=0.017) and those who had knowledge of food nanotechnology (nano food) (p=0.000). Those who think that smart packaging systems that provide information about the quality of packaged food during storage and transportation will not be useful (p=0.001), those who think that smart packaging methods will be preferred instead of traditional packaging techniques with the development of nanotechnology (p=0.000), have ethical concerns about the use of nanotechnology in the field of food. The level of knowledge and awareness about food nanotechnology was found to be high among those who thought that the use of nanotechnology in the field of food was very low (p=0.000) and those who stated that the perceived risk level was very low (p=0.000). It shows that nutrition and dietetics students have limited knowledge about the wide application of food nanotechnology.